A case of schizophrenia with relapsed catatonia successfully treated with blonanserin transdermal patch. Issue 1 (18th January 2023) - Hagikura, Minako; Inada, Toshiya
Abstract: Background: Catatonia is a syndrome that may present with stupor, immobility, and postural retention, and appears in various primary disorders including schizophrenia, depressive disorders, and neurodevelopmental disorders. Case presentation: In this report, we describe a 34‐year‐old female patient with schizophrenia, who had previously been treated with antipsychotic agents to improve psychotic symptoms with delusional symptoms and catatonia. However, she relapsed with catatonic symptoms around 1 year after she voluntarily discontinued the prescribed antipsychotic medications by herself. Her catatonia was successfully improved using the transdermal blonanserin patch, a drug formulation globally first approved in Japan in 2019. Discussion: Although benzodiazepines or electroconvulsive therapy have been recommended as the first‐line treatment of catatonic manifestation observed in psychiatric patients, this patient responded well to antipsychotic blonanserin. From the differential drug responses, catatonia may be the complex of heterogeneous conditions with different pathophysiologies. Abstract : We describe a 34‐year‐old female patient with schizophrenia, who had previously been treated with antipsychotic agents to improve psychotic symptoms with delusional symptoms and catatonia. However, she relapsed with catatonic symptoms around 1 year after she voluntarily discontinued the prescribed antipsychotic medications by herself. Her catatonia was successfully improved using the transdermal blonanserin patch.